2001
DOI: 10.1093/oxfordjournals.molbev.a003811
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Divergence Time Estimation Method under a Probabilistic Model of Rate Evolution

Abstract: Rates of molecular evolution vary over time and, hence, among lineages. In contrast, widely used methods for estimating divergence times from molecular sequence data assume constancy of rates. Therefore, methods for estimation of divergence times that incorporate rate variation are attractive. Improvements on a previously proposed Bayesian technique for divergence time estimation are described. New parameterization more effectively captures the phylogenetic structure of rate evolution on a tree. Fossil informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
528
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 589 publications
(540 citation statements)
references
References 15 publications
4
528
0
8
Order By: Relevance
“…Due to the lack of crown Loliinae fossils, we first estimated the divergence time of the grass family and that dated the divergence of the Triticeae tribe from the Aveneae-Poeae tribe (which include both our outgroup and ingroup taxa) using Bayesian dating methods (Thorne et al, 1998;Kishino et al, 2001;Thorne and Kishino, 2002) as indicated in and Forest et al (2007). Following Gaut (2002), the inferred dates were derived from the plastid gene ndhV of nine Poaceae representatives [Anomochloa (Anomochloeae), Leersia (Oryzeae); Avena (Aveneae); Poa (Poeae); Hordeum (Triticeae); Setaria and Pennisetum (Paniceae); Sorghum and Zea (Andropogoneae) plus Joinvillea (Joinvilleaceae; outgroup)], and a phylogeny of the family concordant with that presented by Clark et al (1995) and the Grass Phylogeny Working Group (GPWG, 2001).…”
Section: Divergence Time Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of crown Loliinae fossils, we first estimated the divergence time of the grass family and that dated the divergence of the Triticeae tribe from the Aveneae-Poeae tribe (which include both our outgroup and ingroup taxa) using Bayesian dating methods (Thorne et al, 1998;Kishino et al, 2001;Thorne and Kishino, 2002) as indicated in and Forest et al (2007). Following Gaut (2002), the inferred dates were derived from the plastid gene ndhV of nine Poaceae representatives [Anomochloa (Anomochloeae), Leersia (Oryzeae); Avena (Aveneae); Poa (Poeae); Hordeum (Triticeae); Setaria and Pennisetum (Paniceae); Sorghum and Zea (Andropogoneae) plus Joinvillea (Joinvilleaceae; outgroup)], and a phylogeny of the family concordant with that presented by Clark et al (1995) and the Grass Phylogeny Working Group (GPWG, 2001).…”
Section: Divergence Time Estimationmentioning
confidence: 99%
“…We used as calibration lower and upper bounds previously reported on the age of the family based on pollen (Linder, 1987;Jacobs et al, 1999;Kellogg, 2002Kellogg, , 2001) and phytoliths (Prasad et al, 2005) fossil records that varied between 55-80 My and that were imposed as minimum and maximum constraints to the crown node of the Poaceae, respectively. Divergence times and additional parameters (based on the F84 + G model and 100,000 MCMC iterations, with rttm and rttmsd set at 6.0, rtrate and rtratesd set at 0.02, brownmean and brownsd set at 0.16, and big time set at 100, see below) were calculated using the programs Baseml (PAML package, Yang, 1997), Estbranches (Thorne et al, 1998) and Multidivtime (Kishino et al, 2001).…”
Section: Divergence Time Estimationmentioning
confidence: 99%
“…Node age estimates were therefore obtained by fitting a relaxed clock model to our molecular data. The assumption of the molecular clock was relaxed by allowing rates of molecular evolution to vary along the tree according to a Brownian motion model (Kishino et al, 2001;Thorne et al, 1998). First, an F84 model with rate variation across sites following a discrete gamma distribution with 20 rate categories was optimized in PAML v.4 (Yang, 2007), using the topology obtained with Bayesian inference from which all but two outgroups were removed (Trentepohlia and Oltmannsiellopsis).…”
Section: Relaxed Molecular Clockmentioning
confidence: 99%
“…Additionally, a Bayesian dating method was used to infer divergence time estimates and associated confidence intervals (Kishino et al, 2001). The procedure outlined in Rutschmann (2005) was followed, which involves the use of three programs: Baseml (PAML3.15; Yang, 1997), Estbranches (Thorne et al, 1998), and Multidivtime (Thorne and Kishino, 2002).…”
Section: Molecular-clock Analysesmentioning
confidence: 99%